Strategi Pengembangan Produk Tabungan Haji Pasca Pandemi Covid-19 Pada BMT UGT Nusantara Capem Sepanjang - Subas, Subas (El-kahfi | Journal of Islamic Economics, 2023)
The Covid-19 pandemi has made the implementation of the hajj abolished and even the registration of the hajj pilgrimage has also decreased. This also has an impact on BMT UGT Nusantara Capem Sepanjang, namely the decline in the number of hajj savings customers. The purpose of the study was to determine the strategy for developing hajj saving products and the obstacles in implementing strategies for developing hajj savings products. This of this study are a strategy for developing hajj savings products. This research method is a qualitative research using secondary data and primary data. The results of this study are a strategy for developing hajj savings products during the Covid-19 pandemic at BMT UGT Nusantara Capem Sepanjang using the follong strategis: 1) Marketing is a complex activity in an effeort to convey product or service information, offers an negotiations, product distribution to consumenrs through promotion an sales. 2) Research an defolopment is a research on existing products to be further developed so that they have a higher usability level and are preferred by cunsumers.